Stealth monoolein-based nanocarriers for delivery of siRNA to cancer cells - Oliveira, Ana Cristina Norberto Gonçalves (2015)
While the delivery of small interfering RNAs (siRNAs) is an attractive strategy to treat several clinical con- ditions, siRNA-nanocarriers stability after intravenous administration is still a major obstacle for the development of RNA-interference based therapies. But, although the need for stability is well recognized, the notion that strong stabilization can decrease nanocarriers efficiency is sometimes neglected. In this work we evaluated two stealth functionalization strategies to stabilize the previously validated dioctade- cyldimethylammonium bromide (DODAB):monoolein (MO) siRNA-lipoplexes. The nanocarriers were pre- and post-pegylated, forming vectors with different stabilities in biological fluids. The stealth nanocarriers behavior was tested under biological mimetic conditions, as the production of stable siRNA-lipoplexes is determinant to achieve efficient intravenous siRNA delivery to cancer cells. Upon incubation in human serum for 2 h, by fluorescence Single Particle Tracking microscopy, PEG-coated lipo- plexes were found to have better colloidal stability as they could maintain a relatively stable size. In addi- tion, using fluorescence fluctuation spectroscopy, post-pegylation also proved to avoid siRNA dissociation from the nanocarriers in human serum. Concomitantly it was found that PEG-coated lipoplexes improved cellular uptake and transfection efficiency in H1299 cells, and had the ability to silence BCR-ABL, affecting the survival of K562 cells. Based on an efficient cellular internalization, good silencing effect, good siRNA retention and good col- loidal stability in human serum, DODAB:MO (2:1) siRNA-lipoplexes coated with PEG-Cer are considered promising nanocarriers for further in vivo validation. Statement of Significance This work describes two stealth functionalization strategies for the stabilization of the previously validated dioctadecyldimethylammonium bromide (DODAB):monoolein (MO) siRNA-lipoplexes. These nanocarriers are capable of efficiently incorporating and delivering siRNA molecules to cells in order to silence genes whose expression is implicated in a pathological condition. The main objective was to functionalize these nanocarriers with a coating conferring protection to siRNA in blood without compromising its efficient delivery to cancer cells, validating the potential of DODAB:MO (2:1) siRNA-lipoplexes as therapeutic vec- tors. We show that the stealth strategy is determinant to achieve a stable and efficient nanocarrier, and that DODAB:MO mixtures have a very promising potential for systemic siRNA delivery to leukemic cells.